Successive harvests affect the aromatic and polyphenol profiles of novel catnip (Nepeta cataria L.) cultivars in a genotype-dependent manner - Gomes, Erik Nunes; Patel, Harna; Yuan, Bo; Lyu, Weiting; Juliani, H. Rodolfo; Wu, Qingli; Simon, James E. (Frontiers in Plant Science, 2023)
Catnip (Nepeta cataria L.) produces volatile iridoid terpenes, mainly nepetalactones, with strong repellent activity against species of arthropods with commercial and medical importance. Recently, new catnip cultivars CR3 and CR9 have been released, both characterized by producing copious amounts of nepetalactones. Due to its perennial nature, multiple harvests can be obtained from this specialty crop. This study aimed to assess the chemical composition of the essential oil and polyphenol accumulation of new catnip cultivars CR3 and CR9 and their hybrid, CR9×CR3, across four successive harvests. Although the effects on biomass accumulation were independent of genotypes, the aromatic profile and the accumulation of polyphenols had a clear genotype-dependent response to successive harvests. While cultivar CR3 had its essential oil dominated by E,Z-nepetalactone in all four harvests, cultivar CR9 showed Z,E-nepetalactone as the main component of its aromatic profile during the 1st, 3rd and 4th harvests. At the second harvest, the essential oil of CR9 was mainly composed of caryophyllene oxide and (E)-β-caryophyllene. The same sesquiterpenes represented the majority of the essential oil of the hybrid CR9×CR3 at the 1st and 2nd successive harvests, while Z,E-nepetalactone was the main component at the 3rd and 4th harvests. For CR9 and CR9×CR3, rosmarinic acid and luteolin diglucuronide were at the highest contents at the 1st and 2nd harvest, while for CR3 the peak occurred at the 3rd successive harvest. Caffeic acid, luteolin, luteolin glucoside and glucuronide, and apigenin glucoside, glucuronide and diglucuronide were accumulated in the highest amounts for all genotypes at the 3rd successive harvest. This is the first report on the effects of successive harvest on these novel catnip genotypes and highlights their potential for the supply of natural products for the pest control and other industries.